Ketidakpastian Hukum Kewenangan Lembaga Pembentuk Undang-Undang Akibat Pengabaian Putusan Mahkamah Konstitusi - Widiarto, Aan Eko (Mahkamah Konstitusi Republik Indonesia, 2015)
The Indonesian House of Representatives and the President has established the Act Num. 17 Year 2014 on MPR, DPR, DPD, and the DPRD (Act MD3). The Act consists provisions that have been declared incompatible with the Constitution 1945 and does not have binding legal force by the Constitutional Court Decision Num. 92/PUU-X/2012. The result is a duality norm. The first norm is the norm authorizes the establishment of laws that have already been decided in the judgment of the Constitutional Court No. 92/PUU-X/2012. The second norm is the new norm about authority of making laws specified in the Act MD3. Both of norms are contrary, so in the implementation (rechtstoepassing), House of Representatives, and the President is faced with two choices provisions of legislation. DPD authority in making the draft law becomes blurred. Similarly for the House of Representatives and the President also no certainty authority in relationship with DPD in the act making process. Should the House of Representatives and the President uphold the principle of self respect or self obidence (the government should respect the decisions of the judiciary).